THE ISSUES OF THE DEVELOPMENT STRATEGY FORMATION OF AUTOMOBILE INDUSTRY COMPANIES IN UKRAINE - Simkova, Tetyana; Borysiuk, Iryna (Proceedings of National Aviation University (archive), 2016)
Purpose: The purpose this study of is to consider the problems to ensure the efficiency of of automobile industry enterprise, to identify measures and areas of improvement and optimization of freight trucking companies and to prove the methods and ways to optimize cargo transportation process, which will give the opportunity to influence the technical level of the new technology and production as a whole. Methods: Monitoring and researching problems ensure, trucking companies, classification and description of components improve the management and optimization of transportation that will enable to transport enterprises to influence the design of the transportation process efficiency, reduce transportation costs and production as a whole. Correlation-regression analysis of the effectiveness determining rational route of vehicles that can improve the technical and operational performance of the rolling stock, increase productivity and reduce the cost of cars of cargo. Results: identified areas to ensure the efficiency of transportation companies automotive industry through the development and adoption of decisions on optimization of freight trucking companies through the development of rational route of vehicle design proposals from warehouse management (number) vehicle fleet, improvement of dispatching service and optimization of organizational structure . Discussion: identifying areas of improvement of transport enterprises automotive industry due to the need to increase the volume of freight traffic, increase usage of rolling stock, saving material and energy resources, reduce labor costs. Decision-making to improve the management and optimization of freight is an important topic for future research, which will create an opportunity for the company to influence the technical level of the new technology and production as a whole.